Південний рубіж роменської культури - Пуголовок, Ю.Ю. (Археологія і давня історія України, 2019)
У статті розглянуто пам'ятки літописних сіверян, що розташовані в середній та нижній течіях
річок Псла та Ворскли. На підставі археологічних
матеріалів окреслено їх територіальну структуру. Окрім цього уточнено південні межі поширення
роменської культури. The article deals with the monuments of the chronicles Siverians, located in the middle and lower
reaches of the Pesl and Vorskla rivers. On the basis of archaeological materials, their territorial structure
is outlined. In modern scientific literature, there is a fairly established view that the carriers of the Romny
culture were chosen to resettle the area that dominated the surrounding and used as much as possible the
natural conditions for their protection. From this, the characteristic of the Romny settlements as a hillfort
was followed. However, with the growth of the source base, there is a certain change in the views. So, now
researchers of the Romny culture noted the predominance of open settlements over the hillforts.
But it is fixed much in Poseymya. According to available archaeological sources, in the south-eastern
borders of the Siverians, such predominance of open settlements over the hillforts does not exist. In the vicinity
of almost fortification of the Romny culture there is only one settlement, although in some cases they are
not recorded at all. It is possible that such placement of monuments is a specific feature of this territory, so
to speak, a certain form of adaptation of the Siverian population to life on the steppe border. Note that in the
Siversky Donets basin, on the border with the Khazar Kaganate, there are still unknown open settlements,
and the most important type of settlements is the fortification itself — the hillfort. Thus, in the southern
Siverian borders four groups of monuments are allocated. There are Zhurvanska and Poltava groups
of monuments are located on Vorskla; on Psel — Kamenska and Nizhnio-Pisilska. In this regard, the
southern boundaries of the spread of the Romny culture pass through the New Sanzhary — Ostapie — Lukimya.